Effects of nitrogen input on soil bacterial community structure and soil nitrogen cycling in the rhizosphere soil of Lycium barbarum L. - Li, Yuekun; Zou, Nan; Liang, Xiaojie; Zhou, Xuan; Guo, Shuhan; Wang, Yajun; Qin, Xiaoya; Tian, Yehan; Lin, Jin (Frontiers in Microbiology, 2023)
Lycium barbarum L., goji berry, is a precious traditional Chinese medicine and food supplement which is heavily dependent on nitrogen for its growth. The use of chemical fertilizers has significantly promoted the growth of goji berry and the sustainable development of the L. barbarum L. industry. However, crop plants are inefficient in the acquisition and utilization of applied nitrogen, which often results in over-applying nitrogen fertilizers by producers, which can ultimately negatively impact the environment. The exploration of an interaction model which deals with crops, chemical fertilizers, and rhizosphere microbes, with higher nitrogen use efficiency, is, therefore, an important research objective to achieve greater agricultural sustainability. In our study, we explored the effects of nitrogen input on soil microbial community structure, soil nitrogen cycling, and the contents of nutrients in L. barbarum fruits. The structure and composition of the bacterial community in the rhizosphere soil of L. barbarum were significantly different under different nitrogen supply conditions, and high nitrogen addition inhibited the diversity and stability of bacterial communities. Low nitrogen input stimulated the relative abundance of ammonia-oxidizing bacteria (AOB), such as Nitrosospira, catalyzing the first step of the ammonia oxidation process. The results of the GLMM model showed that the level of nitrogen fertilizer (urea) input, the relative abundance of AOB, the relative abundance of Bradyrhizobium, and their combinations had significant effects on the soil nitrogen cycling and contents of nutrients in L. barbarum fruits. Therefore, we believe that moderately reducing the use of urea and other nitrogen fertilizers is more conducive to improving soil nitrogen use efficiency and Goji berry fruit quality by increasing the nitrogen cycling potential of soil microorganisms.